(untitled) (Research, Society and Development, 2024)
HPV is the main cause of cervical cancer, which is the fourth leading cause of cancer death among women in Brazil, and can also cause other types of cancer. The quadrivalent HPV vaccine is offered free of charge by the SUS for children aged 9 to 14 years and specific groups, in a single dose. The research seeks to understand the social factors that influence vaccination adherence, aiming to develop more effective and equitable strategies. By investigating the social determinants of health of vaccine uptake, the study aims to provide information for educational programs and community initiatives that help reduce disparities and improve vaccination coverage. The central research question is: what are the main social determinants that affect adherence to HPV vaccination? The study is an integrative review with a qualitative approach, with a search carried out in the LILACS, SCIELO, MEDLINE and BDENF databases, using the PICO strategy and Boolean operators. The study highlights the need for public policies that promote equity in vaccine distribution and involve society, health professionals, educators and family members, in addition to adapting vaccination strategies to regional realities to increase immunization rates.